(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The main idea (conception) of coil mining and processing of Kazakhstan deposits, which summarizes in elaboration and use of modern coil gasification, hydrogenization and briquetting methods.